Compulsory education laws or incentives from CCT programs? Explaining the rise in secondary school attendance rate in Argentina - Maria Edo; Mariana Marchionni; Santiago Garganta (Arizona State University, 2017)
Argentina has traditionally stood out in terms of educational outcomes among its Latin American counterparts. Schooling of older children, however, still shows room for improvement especially among the more vulnerable. Fortunately, during the last years a sizeable improvement in attendance rates for children aged 15 through 17 took place. This could be related to the 2006 National Education Law that made upper-secondary education compulsory. In this paper, instead, we claim that the Asignación Universal por Hijo (Universal Child Allowance, AUH) -a massive conditional cash transfer program implemented in 2009 in Argentina- may be mostly responsible for this improvement. Using a difference-in-difference strategy we estimate that the program accounts for a 3.9 percentage point increase in the probability of attending secondary school among eligible children aged 15 through 17. The impact seems to be led by boys and is more relevant for children living in larger families where the head of household has a lower educational level.